Practical emergency and critical care veterinary nursing - Aldridge, Paul.; O'Dwyer, Louise; Wiley eBooks (Chichester, West Sussex : Wiley-Blackwell, 2013)
This book provides vital information for emergency and critical care situations, whether youre looking for confidence in handling emergency cases in a first-opinion practice, or a relevant, succinct guide for an emergency clinic.
Triage and assessment of emergency patient -- Monitoring critical patients -- Vascular access -- Shock and intravenous fluid therapy -- Blood gas, acid-base analysis, and electrolyte abnormalities -- Analgesia and anaesthesia of the emergency and critical patient -- Practical laboratory techniques -- Techniques for oxygen supplementation -- The dyspnoeic patient -- Nursing the cardiac patient -- Nursing the acute abdomen patient -- Nursing urinary tract emergencies -- Nursing the poisoned patient -- Nursing the trauma patient -- Nursing the reproductive patient -- Small animal critical care and hospitalised patient nutrition -- Nursing the emergency ophthalmology patient -- Cardiopulmonary arrest and resuscitation -- Nursing considerations in the critical patient.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Veterinary nursing; Veterinary emergencies; Veterinary critical care; Animal Diseases -- nursing; Critical Care -- methods; Emergencies -- veterinary; Veterinary critical care; Veterinary emergencies; Veterinary nursing; MEDICAL -- Veterinary Medicine -- Food Animal; MEDICAL -- Veterinary Medicine -- Small Animal; Veterinary critical care; Veterinary emergencies; Veterinary nursing; Animal Diseases -- nursing; Critical Care -- methods; Emergencies -- veterinary; Electronic books